Methodology for estimating the ground heat absorption rate of Ground Heat Exchangers - Stylianou, Iosifina Iosif; Florides, Georgios A.; Tassou, Savvas A.; Tsiolakis, Efthymios; Christodoulides, Paul (My University, 2017)
In Ground Source Heat Pump systems, the heat exchange rate is an important factor with regard to the initial cost of the system. When the Ground Heat Exchanger (GHE) is installed in a lithology with high thermal properties in the presence of groundwater, the heat exchange rates are larger than in the cases with poor thermal response of the ground and no groundwater. This research, hence, focuses on a methodology of measuring and analyzing the thermal properties of the lithologies encountered in an area, which can be used for the prediction of heat injection rates of a GHE, depending on its characteristics, the installation area ground properties and groundwater flow. A tool was created with the use of FlexPDE software, and a study case was chosen in order to validate the results. Twenty-two, 100 m in depth, boreholes located in Lefkosia (Cyprus) were tested through simulation for their geothermal performance over time. Subsequently the estimated heat load for the boreholes, after 24 h of operation in cooling mode, was used with the help of Geographic Information System software for the compilation of a heat load per meter depth map that can be transferred to the ground by a GHE. A review of similar studies and Geographical Information System applications referring to other countries is also presented and their results are compared to the results of this study. The step by step procedure presented in this paper can be used by engineers handling geothermal projects as a useful guide for sizing GHEs and calculating the heat injection rates of any area.
Keywords: Geothermal energy; GIS; Ground geothermal properties; Ground Heat Exchangers; Heat load; Low enthalpy systems